Makanan Adat pada Acara Manjapuik Marapulai di Desa Bayur Kecamatan Tanjung Raya Maninjau - Yorian, Jeni Silvi; Elida, Elida; Holinesti, Rahmi (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2016)
The purposes of the research are to describe : the series of events, varieties of traditional food, the tools used to serve the traditional food in Manjapuik Marapulai in bayur village of tanjung raya maninjau. regency and to analyze the representative meaning of each traditional food served in Manjapuik Marapulai in bayur village of tanjung raya maninjau Regency. It is a qualitative research. The data are collected through snowball sampling technique. The informants are Bundo Kaduang, Ninik Mamak, and some middle-aged female inhabitants in the area. The datas are taken through observation, Interview and documentation. The data analyses are data reduction, data presentation and data conclusion. The resultof the study are as follows. 1) the series of events in Manjapuik Marapulai :a) preparation - cooking the traditional food, the arrangement of jamba gadang, the food arrangement for Manjapuik Marapulai b) the events of Manjapuik Marapulai; Baarak to Marapulai's house, jamba gadang presenting, pepatah petitih, makan basamo, baarak, basandiang. 2) Traditional food in Manjapuik Marapulai : rice, kalio daging, galami , cake, gulai cubadak kicuah, pangek. 3) The tools to serve the food in Manjapuik Marapulai: talam and dulang, carano and its cloth cover, ceper plate, aleh talam, samba plate, cambung. 4) The representive meaning behind the traditional food in Manjapuik Marapulai in Bayur Village of Tanjung Raya Maninjau Regency. The food arrangements in Manjapuik Marapulai reflects the bride's family reputation since the marapulai family will evaluate its jamba gadang content unwittingly. it is an imprortant part of manjapuik marapulai ritual as a requisition of the whole process in Manjapuik Marapulai.Keywords: Manjapuik Marapulai, Traditional food